Synthesis of the nickel-cobalt-manganese cathode material using recycled nickel as precursors from secondary batteries - Jung, Hang Chul; Han, Deokhyun; Kim, Dae Weon; Ahn, Byungmin (Archives of Metallurgy and Materials, 2021)
As the amount of high-capacity secondary battery waste gradually increased, waste secondary batteries for industry (high-speed train & HeV) were recycled and materialization studies were carried out. The precipitation experiment was carried out with various conditions in the synthesis of LiNi0.6Co0.2mn0.2o2 material using a Taylor reactor. The raw material used in this study was a leaching solution generated from waste nickel-based batteries. The nickel-cobalt-manganese (NCm) precursor was prepared by the Taylor reaction process. material analysis indicated that spherical powder was formed, and the particle size of the precursor was decreased as the reaction speed was increased during the preparation of the NCm. The spherical NCm powder having a particle size of 10 µm was synthesized using reaction conditions, stirring speed of 1000 rpm for 24 hours. The NCm precursor prepared by the Taylor reaction was synthesized as a cathode material for the LiB, and then a coin-cell was manufactured to perform the capacity evaluation.
Keywords: High speed train (HST); Leaching solution; Material analysis; Nickel-based batteries; Reaction conditions; Reaction process; Reaction speed; Spherical powders; Cathode materials; Nickel; Recycling; Secondary Battery; Taylor Reaction